2017
DOI: 10.18632/oncotarget.20869
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous silencing of TGF-β1 and COX-2 reduces human skin hypertrophic scar through activation of fibroblast apoptosis

Abstract: Excessive skin scars due to elective operations or trauma represent a challenging clinical problem. Pathophysiology of hypertrophic scars entails a prolonged inflammatory and proliferative phase of wound healing. Over expression of TGF-β1 and COX-2 play key regulatory roles of the aberrant fibrogenic responses and proinflammatory mediators. When we silenced TGF-β1 and COX-2 expression simultaneously in primary human fibroblasts, a marked increase in the apoptotic cell population occurred in contrast to those o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 34 publications
1
41
0
Order By: Relevance
“…While the reduction of inflammatory response with early wound closure achieved by Celecoxib application at early time point could be attributed to its direct anti-inflammatory effect [62][63][64]. The improved scar quality could be attributed to an indirect antifibrotic effect of Celecoxib through reducing wound TGF Beta-1 [61,62] with subsequent reduction in collagen deposition and scar formation [89].…”
Section: Discussionmentioning
confidence: 99%
“…While the reduction of inflammatory response with early wound closure achieved by Celecoxib application at early time point could be attributed to its direct anti-inflammatory effect [62][63][64]. The improved scar quality could be attributed to an indirect antifibrotic effect of Celecoxib through reducing wound TGF Beta-1 [61,62] with subsequent reduction in collagen deposition and scar formation [89].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of TGF‐β1 assembles and TGF‐β‐receptor complex activated the Smad2/3 and JNK signalling in fibroblasts and exhibited the biological behaviour of myofibroblasts . On the contrary, silencing TGF‐β1 resulted in lower collagen synthesis and alleviative scarring which suggested it was a potential therapeutic target for limiting scar formation . High levels of TGF‐β1 may stimulate the activation of detrimental myofibroblasts, but blocking TGF‐β1 completely shows spontaneous skin inflammation and defective vasculogenesis in TGF‐β1 knockout mouse, which indicated that maintaining a certain level of TGF‐β1 in wounds was essential.…”
Section: Biotherapy Aimed At Main Cytokines and Protein Involved In Hssmentioning
confidence: 99%
“…149 On the contrary, silencing TGF-β1 resulted in lower collagen synthesis and alleviative scarring which suggested it was a potential therapeutic target for limiting scar formation. 150 High levels of TGF-β1 may stimulate the activation of detrimental myofibroblasts, but blocking TGF-β1 completely shows spontaneous skin inflammation and defective vasculogenesis in TGF-β1 knockout mouse, 151 which indicated that maintaining a certain level of TGF-β1 in wounds was essential. What we need to do now is to pay attention to the expression level of TGF-β1 in scarfree repair wounds, and to the temporal and spatial dynamics of TGF-β1 to control the homeostasis of reepithelialisation, vascularization, and inflammation.…”
Section: Biotherapy Aimed At Main Cytokines and Protein Involved Inmentioning
confidence: 99%
“…Periodically collected samples of the granulation tissue from wound sites using predominantly a rodent model are usually evaluated (Nascimento and Costa 2006;Gercek et al 2007;Otranto et al 2010;dos Santos Rosa et al 2014;Ramanathan et al 2017;Sathyanarayanan et al 2017;Zhou et al 2017). As far as histological preparations are concerned, samples of the healing tissue including ca 2 mm of skin surrounding the wound are usually taken, fixed in 10% buffered formalin, dehydrated by a gradual alcohol series, cleared in xylene, embedded in paraffin blocks, sectioned into a size of (usually) 5 µm thickness, stained with haematoxylin-eosin (H&E) and observed under light microscopy.…”
Section: Histopathology and Immunohistochemistry (Ihc) Of Cutaneous Wmentioning
confidence: 99%
“…Rabbit polyclonal IgG (Ramanathan et al 2017) or mouse monoclonal antibody (Otranto et al 2010;dos Santos Rosa et al 2014) are usually used as a primary antibody for immunostaining. Goat anti-rabbit antibody (Zhou et al 2017) and biotinylated anti-rat antibody (dos Santos Rosa et al 2014) are frequently applied secondary antibodies in this context. The last mentioned authors (dos Santos Rosa et al 2014) also used an anti-mouse secondary antibody conjugated with Alexa Fluor 647 for the detection of epithelial cadherin (E-cadherin) when evaluating cutaneous wound healing in mice.…”
Section: Histopathology and Immunohistochemistry (Ihc) Of Cutaneous Wmentioning
confidence: 99%